Studies of productive traits in a New Zealand Romney flock : the effect of some environmental factors, heritabilities and repeatabilities : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Science at Massey University - Lundie, Roger Scott (Massey University, 1971)
Three traits of dual purpose sheep such as the New Zealand Romney are of paramount importance in contributing directly to income. These are reproductive ability and wool production of the ewe flock and the growth rate of the lamb produced. Investigations of methods of genetic improvement of these traits is important, since such improvement is more permanent than that caused by environmental modification or the use of hormones. Improvement of productive traits through genetic means may be brought about (1) by exploiting the differences between groups of animals which have been genetically distinct for some time (breeds, strains, studs or inbred lines) or (2) by exploiting the difference between individual animals within a flock, The first method involves crossbreeding, which may change production through the introduction of superior genes or through complex interactions between genes (heterosis and epistasis). Rae (1952) reviewed the field of crossbreeding and looked at grading up existing breeds, combining crossbreeding with selection to form new breeds and exploiting hybrid vigour (heterosis). With the N.Z. Romney this practice is in fact being carried out by some farmers who are crossing with the Cheviot (to obtain an animal for a harsh environment) or Border Leicester (for a more favourable environment). In some cases these crossbred animals so produced have been interbred and selected to form the two new breeds Perendale and Coopworth respectively. For many reasons many farmers prefer not to cross their flocks with animals of another breed and it is then necessary to use the second method, i.e. to select within the farmers flock, if any genetic improvement is to be acheived. This study is aimed at studying factors of importance to within flock selection.
Keywords: Romney Marsh sheep; Breeding; Growth; Economic aspects; Livestock productivity; New Zealand